2015
DOI: 10.1186/s12864-015-2172-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNAs and isomiRs in the porcine endometrium: implications for gene regulation at the maternal-conceptus interface

Abstract: BackgroundEmbryo implantation is a complex, synchronized process that requires establishment of a reciprocal dialogue between a receptive endometrium and developing blastocysts. Recently, microRNAs (miRNAs), known to modulate gene expression through post-transcriptional mechanisms, were implicated in regulation of early pregnancy events including maternal recognition of pregnancy and implantation. To characterize complex transcriptomic changes, expression of miRNAs in pregnant and cyclic endometria collected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 65 publications
0
71
0
Order By: Relevance
“…We found that restricted diet may decrease the expression of genes encoded proteins which are involved in the formation of exosome vesicles in the endometrium (Tannetta, Dragovic, Alyahyaei, & Southcombe, ). It was found that exosomes may contain miRNA that contributes to proper development of endometrial‐embryo cross‐talk (Krawczynski, Bauersachs, Reliszko, Graf, & Kaczmarek, ). Observed in our study decreased expression of genes involved in the formation of exosome vesicles may indicate that restricted diet during peri‐conceptional period affects the mechanisms of endometrial‐embryo cross‐talk mediated via components of exosome vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…We found that restricted diet may decrease the expression of genes encoded proteins which are involved in the formation of exosome vesicles in the endometrium (Tannetta, Dragovic, Alyahyaei, & Southcombe, ). It was found that exosomes may contain miRNA that contributes to proper development of endometrial‐embryo cross‐talk (Krawczynski, Bauersachs, Reliszko, Graf, & Kaczmarek, ). Observed in our study decreased expression of genes involved in the formation of exosome vesicles may indicate that restricted diet during peri‐conceptional period affects the mechanisms of endometrial‐embryo cross‐talk mediated via components of exosome vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, pregnancy stage-dependent expression profiles of genes involved in miRNA synthesis and transport were demonstrated in porcine conceptuses, trophoblasts, and endometria [22,23]. Uterine glands and luminal epithelia were the only sites of DICER1 and AGO2 immunoreactivity, where miRNA biogenesis seems likely to occur during early pregnancy in pigs.…”
Section: Mirna Biogenesis At the Embryo-maternal Interfacementioning
confidence: 99%
“…Expression profiling has identified a large number of miRNAs in reproductive tissues, including the ovary and the endometrium (Chegini, 2010;Su et al, 2014). Endometrial miRNAs have been associated with the regulation of genes that are important for differentiation, proliferations, receptivity, extracellular matrix factors, angiogenesis, and immunological response processes, which are crucial in preparation of the endometrium for implantation (Bidarimath et al, 2014;Krawczynski, Bauersachs, Reliszko, Graf, & Kaczmarek, 2015;Wessels et al, 2013). Steroid hormones and their respective receptors such as estrogen receptors (ER) α and β largely control these processes (Chegini, 2010).…”
mentioning
confidence: 99%